Języki w kontakcie. Fenomen słowiańskiej komunikatywności - Hofmański, Wojciech (Slavia Occidentalis, 2012)
This article discusses the results of an analysis of the functioning of the psycholinguistic phenomenon of inter-language communication within Slavonic languages. A particular emphasis is put to one of the key elements of this phenomenon, i.e., the dysfunction in and disturbance to the perception of delimitation of distinctive and delimitative functions of phonological features that in the initial stage of the language contact result in an obstruction to the functioning of cognitive mechanisms (responsible for processing the meaning of common or analogous morphemes and lexemes occurring in a linguistic system closely related to the Polish language). The experiments described in the article provided reliable data to determine and document not only the reasons behind the occurrence of these problems in understanding utterances (communiques) in some other Slavonic languages, relatively easy to overcome, but also to indicate the disproportion, commonly perceived, between the productive and receptive competence – with the example of the experiment participants involved in thus embedded glottodidactical process.